The Impact of Obesity and Nutrition Habits on Gynecomastia among Turkish Adolescent Males - OLUKLU, MUSTAFA TAYGUN (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2021)
Introduction: Gynecomastia (GM) during adolescence is quite common and represents a serious psychological challenge among young males. Obesity is also one of the major public health problems affecting an important proportion of the population. We studied the relationship between nutritional habits, body mass index (BMI), and GM of adolescent males. Materials and Methods: In this study, we report an analysis of the incidence of GM and its relationship with nutrition habits and BMI among 511 randomly selected high-school students between 16 and 18 years of age from schools located in Pendik municipality of Istanbul. Results: We found the incidence of GM of 33.3% (n = 170) in 511 high-school boys of whom 24.8% (n = 127) were classified overweight or obese. Although the mean BMI for the entire group was within the normal range (22.8 +/- 4.4), it was significantly higher in boys with GM compared to the boys without GM, 26.8 +/- 4.5 vs. 20.7 +/- 2.5, respectively (P < 0.001). In addition, boys with stage 2 and higher degree GM had higher BMI compared to those with stage 1 GM, 29.2 +/- 4.5 vs. 24.8 +/- 3.3, respectively (P < 0.001). We, thereby, observed a clear positive correlation between BMI and GM. Conclusion: GM in high-school boys is closely correlated with overweight and obesity. Precautions should be taken to increase awareness of this global health concern to develop comprehensive public health strategies to improve the prevention and management of obesity and related complications like GM.
Keywords: Adolescent; gynecomastia; nutrition habits; obesity; BODY-MASS INDEX; PUBERTAL GYNECOMASTIA; FOOD-HABITS; PREVALENCE; CHILDREN; MATURATION; TRENDS; BOYS